Instructional Supervision in a State University: Needs Analysis for an Evidence-Based Mentoring Program - Marifi M. Malonzo (Future Science / FSH-PH Publications, 2026)
The aim of this study is to determine the instructional supervision needs of college instructors in a state university. A sequential explanatory mixed methods design was used, involving 695 instructors in the quantitative phase and 10 instructional supervision experts in the qualitative phase. Based on the results of the study, college instructors indicated their need to be mentored with direct assistance, professional development, group development, curriculum development, communication skills, mastery of the subject matter, and research. These needs are essential to improving instructors’ competence in delivering quality instruction. Qualitative findings further highlighted the need for evidence-based instructional supervision strategies including the need to provide opportunities for content knowledge enhancement and provision of instructional resources; engaging college instructors in capability enhancement programs; and developing instructional supervision and management practices. The results reveal gaps in both pedagogy and content expertise that affect instructional quality. The mentoring program was proposed as an evidence-based in addressing these gaps, enhancing instructors’ competence, strengthening instructional supervision practices, and contributing to improved student learning outcomes through more effective teaching.